A GENETIC-BASIS FOR FAMILIAL AGGREGATION IN MULTIPLE-SCLEROSIS - Ebers, G; Sadovnick, A; Risch, N; Bulman, D; Rice, G; Hashimoto, S; Paty, D; Oger, J; Metz, L; Bell, R; Warren, S; Hader, W; et al. (1995)
GENETIC-environmental interactions probably underlie spontaneous human autoimmune disorders, a category of complex traits thought to include multiple sclerosis (MS)1. The geographical distribution and familial aggregation of this disease have often been ascribed to the role of infectious agents2, but there is no consensus. Increased family risks range from 300-fold3,4 for monozygotic twins to 20-40-fold5 for biological first-degree relatives over the general population prevalence of 0.1% (ref. 6). We screened a population-based sample of 15,000 individuals with MS by using standardized, personally administered questionnaires to identify adopted index cases and/or those who had adopted relatives. The frequency of MS among first-degree non-biological relatives living with the index case was no greater than expected from Canadian population prevalence data and significantly less than for biological relatives. These findings indicate that familial aggregation of MS is genetically determined: no effect of shared environment was detectable. © 1995 Nature Publishing Group.